GOODS PROCESSING DATA APPLICATION USING MS. VISUAL BASIC 6.0 - Syahril., SKom Syahril., SKom; Debby Hairunisa Tarundjaya (Jurnal Sistem Informasi, 2007)
In this writing, process data processing of goods is essential to avoid errors in therecording process, so that it can obtain accurate information. In order to make dataprocessing report good things and to execute the process in accordance with existingprocedures, it would require an application to facilitate the conduct of data processing.Therefore, the author makes the writing entitled "Data Processing Applications Goods"by using one of Microsoft's programming language Visual Basic 6.0 that can create anapplication program in windows environment.